Pembuatan Membran Antiseptik Dari Kombinasi Kitosan Dan Kulit Jeruk Nipis (Citrus aurantiifolia - Agnes Ayu Biomi; rahayu artini yuan (Universitas Muhammadiyah Surabaya, 2022)
As technology develops, air quality tends to decline. One of the air pollutants that is often encountered is bacteria that infect through the air such as Staphylococcus aureus. As a basic protection tool, a cloth mask with a membrane layer can be an alternative solution. One of the materials that can be used is chitosan and lime peel pectin. Lime peel produces essential oils that are used as stimulant, aromatherapy, and antimicrobial enhancers. This study aims to determine the results of characteristic tests, content analysis through phytochemicals and Staphylococcus aureus. The research method used is descriptive exploratory and experimental. The membrane mask made from chitosan of shrimp skin and lime peel has a characteristic thickness of 00.24 mm with a density of 0.60 - 0.90 g/cm3 with a textured heterogeneous surface. Has a water vapor transmission power of 0.00088 g/day/m2. It takes 27.54 days to completely decompose. Grapefruit peel essential oil contains secondary metabolites in the form of alkaloids, flavonoids, tannins, phenolics and triterpenoids. The membrane mask had Staphylococcus aureus antibacterial activity ranging from 14.05 mm. Keywords: Lime peel (Citrus aurantiifolia), Shrimp Skin Chitosan, Membrane mask, Antibacterial.